The development of the La Sallete College admissions test (LSCAT) - Quiros, Josephine Sillos (Animo Repository, 1987)
This study develops and standardizes an admission test for La Salette College. The proposed La Salette College Admissions Test (LSCAT) will be used as an admission test for first year applicants of the college. The development of the LSCAT involved the following procedures: (1) planning the test (2) item writing and reviewing (3) assembly of the pretest forms (4) pretest administration (5) item analysis and (6) assembly of the final form. There were 273 examinees who took the pretest forms and whose test papers were used in the item analysis. Item analysis was done using the Center for Educational Measurement (CEM) programs especially designed for item analysis. Items which satisfied the criteria set for accepting items composed the final form of the test.Pretest data analysis yielded the following:1. The pretest item difficulty indices as measured by the p ranged from .05 to .95. This means that the pretest forms were composed of very easy to very difficult items.2. The pretest items had a mean discrimination (rbis) of .35. The Verbal Ability items were more discriminating than the Numerical Ability items. Paragraph Organization items were found out to be the most discriminating in the Verbal Ability area, while the items on Sequences were found out to be the most discriminating in the Numerical Ability area.3. Majority of the items have satisfied the criteria set for item acceptability based on option analysis.Final form data analysis yielded the following: 1. The final form had a mean difficulty (p) of .34 with SD of .14. The items on the Numerical Ability area were found out to be more difficult than the Verbal Ability items.2. The final form had a mean discrimination index (rbis) of .40 with SD of .12. The Verbal Ability items were found out to be more discriminating than the Numerical Ability items.In the light of the foregoing findings, the following conclusions were drawn.1. The difficulty level of the final form of the LSCAT is moderately difficult. Hence, the test is appropriate for screening applicants for college admission.2. The final form of the LSCAT is composed of items which have moderately high discrimination indices.3. The LSCAT can assess student's competency in both Verbal and Numerical subject areas.4. The LSCAT can serve as diagnostic measure in determining student's strengths and weaknesses in the areas of Verbal and Numerical subjects.5. The LSCAT can be used as a basis for placement of students in any program of the school.On the basis of the findings and conclusions drawn from this study, the following recommendations are given:1. A comprehensive review of the items be undertaken in order to further improve the test.2. Reliability such as the alternative - form method and split - half method be undertaken.3. Concurrent and predictive validity of the test be determined.4. Norms based on a referenced group be established.